MENGENAL OSTEOGENESIS IMPERFECTA - Uswatun Hasanah (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT   Osteogenesis imperfecta ( OI ) is a group of disorders of bone formation that makes bones brittle abnormally. Osteogenesis Imperfecta , also known as brittle bone disease. OI is a genetic disorder ( legacy ) that is characterized by bones that break easily without a specific cause. This disease occurs due to changes in collagen that forms the basis of bone formation, so that bones tend to be thinner and smaller. The bones become weak and easily cracked . Since 1979, OI has been classified by type according to the system based on the mode of inheritance, clinical features, and information from the x - ray. Four types of osteogenesis imperfecta, namely Type I, Type II, Type III and Type IV. Health problems often seen in children and adults who have OI include: short stature, weak tissues, fragile skin, muscle weakness, and loose joints, bleeding, easy bruising, frequent nosebleeds , and tiny amounts of the heavy bleeding from the wound, impaired loss can begin in childhood and affects approximately 50 % of adults, breathing problems, a higher incidence of asthma plus risk for other lung problems, spinal curvature. Kata Kunci : Osteogenesis imperfecta, genetic, collagen